Bayesian belief networks for the analysis of the controversial role of hydropower development in the antagonistic agrofood-fisheries nexus: A potential approach supporting sustainable development in the Guayas river basin (Ecuador) - De Cock, Andrée; Forio, Marie Anne Eurie; Dominguez-Granda, Luis; Goethals, Peter L. M. (Frontiers in Environmental Science, 2022)
Increasing anthropogenic activities are affecting water quality and related ecosystem services in river basins worldwide. There is a need to identify and act on synergies between the water-energy-food (WEF) elements and the other Sustainable Development Goals (SDGs) while mediating trade-offs. The Guayas river basin (GRB), one of the major watersheds in Ecuador, is being affected by increasing urbanization, agricultural and industrial activities. In this perspective paper, we indicate the WEF interactions in the GRB linked to the SDGs. A major challenge is the geographical distance between pressures and impacts, for which environmental and agricultural governance are key to support the needed change towards sustainable development. In particular, the realization of measures to reduce the pollutant input in upstream systems will need both legislative and financial means to solve downstream water quality problems. A Bayesian belief network (BBN) framework was developed in order to support sustainable decision making in the GRB. The discussed concepts can be applied to other river basins worldwide since, in many basins, very similar food production challenges need to be addressed.